Monitoring Criteria of Intracranial Lesions in Children Post Mild or Moderate Head Trauma - Jacquet, Coralie; Boetto, Sergio; Sevely, Annick; Sol, Jean-Christophe; Chaix, Yves; Cheuret, Emmanuel (Neuropediatrics, 2018)
Head injury is the most common cause of child traumatology. However, there exist no treatment guidelines in children having intracranial lesions due to minor or moderate head trauma. There is little knowledge about monitoring, clinical exacerbation risk factors, or optimal duration of hospitalization. The aim of this retrospective study is to find predictive factors in the clinical course of non-severe head trauma in children, and thus to determine an optimal management strategy. Poor clinical progress was observed in only 4 out of 113 children. When there are no clinical signs and no eating disorders, an earlier discharge is entirely appropriate. Nevertheless, persistent clinical symptoms including headache, vomiting, and late onset seizure, especially in conjunction with hemodynamic disorders such as bradycardia, present a risk of emergency neurosurgery or neurological deterioration. Special attention should be paid to extradural hematoma (EDH) of more than 10 mm, which can have the most severe consequences. Clinical aggravation does not necessarily correlate with a change in follow-up imaging. Conversely, an apparent increase in the brain lesion on the scan is not consistently linked to a pejorative outcome.
Keywords: head trauma; intracranial lesion; child